2018
DOI: 10.7567/jjap.57.061301
|View full text |Cite
|
Sign up to set email alerts
|

Dependences of contraction/expansion of stacking faults on temperature and current density in 4H-SiC p–i–n diodes

Abstract: To investigate the mechanism of contraction/expansion behavior of Shockley stacking faults (SSFs) in 4H-SiC p-i-n diodes, the dependences of the SSF behavior on temperature and injection current density were investigated by electroluminescence image observation. We investigated the dependences of both triangle-and bar-shaped SSFs on the injection current density at four temperature levels. All SSFs in this study show similar temperature and injection current density dependences. We found that the expansion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…The 1SSFs of T1 and T3 had a right-angled corner on the right side, and these two types are the most frequently observed and repo rted. 3,[5][6][7][9][10][11][12][13][14]16,[19][20][21][22] However, the 1SSFs of T2 had a triangular shape with a right-and-left in contrast to T1 and T3. The expansion direction of T2, which was from the surface to the substrate/epilayer interface, was opposite to that of T3.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The 1SSFs of T1 and T3 had a right-angled corner on the right side, and these two types are the most frequently observed and repo rted. 3,[5][6][7][9][10][11][12][13][14]16,[19][20][21][22] However, the 1SSFs of T2 had a triangular shape with a right-and-left in contrast to T1 and T3. The expansion direction of T2, which was from the surface to the substrate/epilayer interface, was opposite to that of T3.…”
Section: Resultsmentioning
confidence: 93%
“…4 Most previous studies on the expansion of 1SSFs have found that the SSFs originate from two kinds of BPDs: one that had penetrated from the substrate into the epilayer, 5,6 and another that had converted to a threading edge dislocation (TED) around the substrate/epilayer interface during epitaxial growth. 7 In addition, many analyses have been conducted of these 1SSFs, including current/temperature stress testing, [8][9][10][11][12][13][14] calculations, [15][16][17][18] and crystal analysis. [19][20][21][22][23] The BPD detection by photoluminescence (PL) imaging and the use of a buffer layer between the substrate and the epitaxial layer was proposed as a method for controlling 1SSF expansion 4,7,11,24 with the aim of solving the V F degradation issue.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Therefore, studies of SSF nucleation and expansion have drawn the attention of many researchers. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, in spite of numerous investigations understanding the SSF behavior is still insufficient and many fundamental questions still remain to be explored. It has been well established that SSFs can be introduced at room temperature in power devices at high forward currents [3][4][5][6][7][8]19,22] or under electron beam or optical irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is promising for the production of bipolar power devices, [1,2] however, a wide application of such devices is currently impeded by the formation and expansion of single-layer Shockley-type stacking faults (SSFs) during forward-bias operation, which significantly degrades device parameters. [3][4][5][6][7] Therefore, studies of SSF nucleation and expansion have drawn the attention of many researchers. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, in spite of numerous investigations understanding the SSF behavior is still insufficient and many fundamental questions still remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation